Così reale da poter essere immaginato: il ruolo dell’immaginazione sociologica e i “fatti sociali” globali - Fabio Massimo Lo Verde; Marco Ciziceno; Marianna Siino (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
The understanding of contemporary economic geographies and global “social facts” represent the best challenge for Burawoy’s public sociology. Scholars wonder whether sociology can successfully address our time’s problems, keeping its spirit of service to the community alive. Indeed, recent political and economic events require formulating a new sociological imagination that is more creative, open, and accessible to the general public. In this paper, we use some of the most significant intersections of Mills’ work, between history and personal biography, to highlight the sociological imagination’s significant role in understanding the present. We use practical cases of applying the concept of sociological imagination close to us, such as the recent COVID-19 pandemic.